2001
DOI: 10.1046/j.1365-3083.2001.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding, Trafficking and Accumulation of Serum Amyloid A in Peritoneal Macrophages

Abstract: Murine serum amyloid A1.1 (SAA1.1) has been conjugated with the fluorophore Texas Red (TxR), and its interaction with peritoneal macrophages has been visualized by scanning confocal microscopy. Binding of TxR±SAA to cell surfaces was inhibited by an excess of unlabelled SAA indicating the involvement of saturable receptors. Internalized TxR±SAA was seen initially as small punctate signals which in some cells evolved into a fine fluorescent network, a pattern typical of tubular endosomes. Colocalization of TxR±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
(26 reference statements)
4
37
0
Order By: Relevance
“…It is possible that once liberated from HDL, SAA undergoes structural changes or becomes susceptible to limited proteolysis and the modified protein triggers inflammasome activation. Our study, consistent with other reports (68,69) indicates that HDL does not prevent cellular uptake of SAA ( Fig.7G and H). According to one report, HDL-SAA is internalized through a clathrin-dependent endocytic pathway and then trafficked to lysosomes where it accumulates as SAA aggregates or amyloid deposits (69).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It is possible that once liberated from HDL, SAA undergoes structural changes or becomes susceptible to limited proteolysis and the modified protein triggers inflammasome activation. Our study, consistent with other reports (68,69) indicates that HDL does not prevent cellular uptake of SAA ( Fig.7G and H). According to one report, HDL-SAA is internalized through a clathrin-dependent endocytic pathway and then trafficked to lysosomes where it accumulates as SAA aggregates or amyloid deposits (69).…”
Section: Discussionsupporting
confidence: 94%
“…Amyloid fibrils can cause disruption of lysosomal membranes (69), which may trigger inflammasome activation. However it seems unlikely that SAA fibril formation is responsible for triggering inflammasome activation in our study, as HDLbound SAA is capable of forming intracellular fibrils (68,69).…”
Section: Discussionmentioning
confidence: 64%
“…Available data about the phagocytic activity and oxidative burst of PMN and monocytes during FMF are very contradictory. Some reports support the decrease in the phagocytic activity of PMN and monocytes [39,40] , while there are no notable changes in others [41,42] , and in studies regarding the mechanism of amyloidogenesis, in contrast, the activation of phagocytosis of monocytes/macrophages is noted as an important pathogenetic link [43] . In addition, a number of subtle abnormalities in PMN function, including enhanced chemiluminescence [44] , chemotaxis [45] , superoxide production [46] and lysozyme leak [40] , have been noted in patients with FMF.…”
Section: Discussionmentioning
confidence: 94%
“…3A), which strongly argues against extracellular SAA fibril formation and phagocytosis-induced inflammasome activation. However, it has been reported that cytochalasin D-independent uptake of SAA by macrophages and subsequent formation of intracellular amyloid fibrils can take place when high SAA concentrations (.100 mg/ml) are used (49). Therefore, we studied whether SAA could induce lysosomal destabilization and leakage of cathepsin B into cytoplasm.…”
Section: Saa-induced Inflammasome Activation Is Dependent On Cathepsin Bmentioning
confidence: 99%